THE INFLUENCE OF LEADERSHIP AND DECISION MAKING ON SOCIAL LIFE IN PIONEER ORGANIZATIONS OF GOOD IN WEST SUMATRA - Dina Adilla Maharani; Syamsir Syamsir; Fadillah Harmi; Nadila Vhitra Januar; Nasywa Dwi Aura; Revi Haryanti; Shafira Ramadhani (Yayasan Amanah Nur Aman, 2026)
This study looks at how leadership and decision-making affect the social aspects of the Pelopor Kebaikan organization in West Sumatra. The research takes a qualitative approach with descriptive methods. Data were gathered through in-depth interviews, observations, and document collection. The Branch Coordinator of Pelopor Kebaikan in West Sumatra was the main informant for this study. The findings reveal that leadership significantly impacts solidarity, member quality, and the organization's sustainability. Leaders play a crucial role in creating an effective system. They achieve this by providing regular training, rewarding active members, and offering discussion forums for all members to share their opinions and feedback. The organization uses two methods for decisionmaking. First, it involves members through deliberation for certain decisions. Second, the leader makes special decisions to ensure the organization runs smoothly and maintains confidentiality. Decision evaluations occur by assessing impacts, conducting surveys among members, and revising decisions if necessary. From the research results, we can conclude that democratic leadership and an open decision-making process foster better social interactions within the organization. This is clear from effective communication, a heightened sense of responsibility among members, and strong solidarity during the organization’s social activities.